2022
DOI: 10.3390/ijms23073422
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Light and Auxin Signaling in Shade Plants: From Mechanisms to Opportunities in Urban Agriculture

Abstract: With intensification of urbanization throughout the world, food security is being threatened by the population surge, frequent occurrence of extreme climate events, limited area of available cultivated land, insufficient utilization of urban space, and other factors. Determining the means by which high-yielding and high-quality crops can be produced in a limited space is an urgent priority for plant scientists. Dense planting, vertical production, and indoor cultivation are effective ways to make full use of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 96 publications
1
6
0
Order By: Relevance
“…Red and blue light maximizes photosynthetic performance and is therefore essential for normal plant growth and development (Kharshiing and Sinha, 2016). In addition, most plants can regulate shade avoidance response by sensing blue and red wavelengths (Xie et al, 2022;Zeidler, 2022). Therefore, blue and red light is essential for plant photomorphogenesis and photosynthetic traits.…”
Section: Introductionmentioning
confidence: 99%
“…Red and blue light maximizes photosynthetic performance and is therefore essential for normal plant growth and development (Kharshiing and Sinha, 2016). In addition, most plants can regulate shade avoidance response by sensing blue and red wavelengths (Xie et al, 2022;Zeidler, 2022). Therefore, blue and red light is essential for plant photomorphogenesis and photosynthetic traits.…”
Section: Introductionmentioning
confidence: 99%
“…Plant hormones interact with COP1 and HY5 and integrate into the light signaling network [ 27 , 28 ]. It was reported that under shade, auxin/IAA and GA were activated to promote stem elongation, MeJA was repressed to attenuate limited resources reallocating to defense, and ABA was increased to repress branching [ 22 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the shortest C. xanthorrhiza plants were found in 25% shade, followed by 0%. Different light conditions cause significant differences in plant morphology, metabolism, and interactions with other organisms [24]. The light intensity hitting plants was adjusted using various shading techniques.…”
Section: Plant Heightmentioning
confidence: 99%